GROWTH AND DEVELOPMENT SOCIAL MEDIA STRATEGIES FOR ENTREPRENEURIAL SUCCESS: A COMPARATIVE STUDY - Irene Hasian; Friska Nurliana (Adisam Publisher, 2025)
This study aims to provide a comparative analysis of social media strategies employed by successful entrepreneurs, with a focus on the role of platforms such as Facebook, Instagram, and Twitter.To investigate this topic, the researchers conducted a bibliometric review of the existing literature. The review explored how entrepreneurial leaders utilize social media, with a particular emphasis on the content and tone of their online communications. The researchers conducted a comprehensive search of academic databases, including Scopus, Web of Science, and Google Scholar, to identify relevant scholarly articles and publications. . The search terms used included a combination of keywords related to social media, entrepreneurship, and business growth, such as